Faktor - Faktor Kepatuhan Penggunaan Obat Antidiabetes Pada Pasien Diabetes Mellitus Tipe 2 di Poli Rawat Jalan Rumah Sakit X di Kabupaten Badung - Suryaningsih, Ni Putu Aryati; Purwahita, Adi; Saraswati, Anak Ayu Sri; Aini, Siti Nur (Bali International Scientific Forum, 2020)
Background: Diabetes mellitus is a symptoms that appears caused by impaired ability of the body to control blood glucose level in the body. Patient medication adherence is important to prevent any complication in diabetes mellitus patients. Purpose: This study aims to know the factors  that influence the use of antidiabetic drugs to the patients of type 2 diabetes mellitus at Outpatient Poly in X Hospital, Badung Regency. Method: Cross sectional method is applied with purposive sampling as the sampling technique. 71 patients with tipe 2 diabetes at Outpatient Poly X hospital has been used as samples on January 2019. Questionnaire has been used as an instrument of the study. Using univariate and bivariate analyses with Chi Square Test and multivariate analyses with Binary Logistic Regretion. Result: The study showed that educational factor (p=0,021) and gender factor (p=0,073) were associated with the factors that affected patient medication adherence. At the mean time, knowledge factor (p = 0,470), status of work (p =0,511), and quantity of drugs (0,964) received were not significantly associated with patient medication adherence at Outpatient Poly in X hospital.. Conclusion: Patient medication adherence in type 2 diabetes mellitus at the Outpatient Poly at X Hospital is influenced by education and gender factors..